2007
DOI: 10.1016/j.freeradbiomed.2007.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Mn porphyrin-based superoxide dismutase (SOD) mimic, MnIIITE-2-PyP5+, targets mouse heart mitochondria

Abstract: The Mn(III) meso-tetrakis(N-ethylpyridinium-2-yl)porphyrin, MnIIITE-2-PyP5+ (AEOL-10113) has proven effective in treating oxidative stress-induced conditions including cancer, radiation damage, diabetes, and central nervous system trauma. The ortho cationic pyridyl nitrogens of MnTE-2-PyP5+ are essential for its high antioxidant potency. The exceptional ability of MnIIITE-2-PyP5+ to dismute O2.- parallels its ability to reduce ONOO- and CO3-. Decreasing levels of these species are considered its predominant mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 62 publications
2
110
0
Order By: Relevance
“…Accordingly, DMPO, L-NAME, Mito-Q, and MnTE-2-PyP restored mitochondrial respiration and also prevented astrocyte-derived neurotoxicity. It has been recently shown that MnTE-2-PyP in the Mn 3ϩ oxidation state is reduced by complex I and complex II of the mitochondrial ETC, and the reduced (Mn 2ϩ ) complex reacts and decomposes peroxynitrite, suggesting that Mn-porphyrins may act as peroxynitrite reduction catalysts in vivo and protect mitochondria from oxidative damage (Ferrer-Sueta et al, 2006;Spasojević et al, 2007). These results emphasize the key role of nitroxidative stress in astrocytes in the pathogenesis of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 86%
“…Accordingly, DMPO, L-NAME, Mito-Q, and MnTE-2-PyP restored mitochondrial respiration and also prevented astrocyte-derived neurotoxicity. It has been recently shown that MnTE-2-PyP in the Mn 3ϩ oxidation state is reduced by complex I and complex II of the mitochondrial ETC, and the reduced (Mn 2ϩ ) complex reacts and decomposes peroxynitrite, suggesting that Mn-porphyrins may act as peroxynitrite reduction catalysts in vivo and protect mitochondria from oxidative damage (Ferrer-Sueta et al, 2006;Spasojević et al, 2007). These results emphasize the key role of nitroxidative stress in astrocytes in the pathogenesis of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 86%
“…It is possible that in order to be effective these SOD mimics or manganese ions have to be in a particular cellular location(s) at sufficient concentration and be in a suitable chemical form to scavenge superoxide. It is interesting in this regard to note that MnTE-2-PyP has recently been demonstrated to target mouse heart mitochondria [43]. The differences in the efficacy observed for some SOD mimics, such as EUK compounds, that work in E. coli and not in yeast could be due to mislocalization or due to lack of sufficient concentration buildup of active species of these compounds in compartments where the radicals are present.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer. Because (a) MnSOD (the essential endogenous antioxidant) is reduced in many cancers; (b) increased expression of MnSOD inhibits cancer growth (152), and (c) SOD mimic, MnTE-2-PyP 5þ enters mitochondria (306), it is only logical that we tested the possible anticancer activity of MnTE-2-PyP 5þ . Three studies from our group were done within the last 8 years (with doses of MnTE-2-PyP 5þ ranging from 6 to 15 mg=kg) with the goal to prove if and why a catalytic SOD mimic=peroxynitrite scavenger would exert anticancer effects [i.e., to evaluate whether the attenuation of the oxidative stress by MnTE-2-PyP 5þ could suppress tumor growth in a 4T1 mouse breast tumor model (222,221,259)].…”
Section: Cancermentioning
confidence: 99%